Struktur Komunitas Cacing Parasitik pada Ikan Kembung (Rastrelliger Spp.) di Perairan Teluk Banten dan Pelabuhan Ratu - Forcep Rio Indaryanto; Yusli Wardiatno; Risa Tiuria (Jurnal Ilmu Pertanian Indonesia, 2014)
The short mackerel is the most commercially important small pelagic fish in Indonesia. Parasitism plays a central role in fish biology. Parasitism is a ubiquitous phenomenon in the marine environment and it is probable that all marine fishes are infected with parasites. Helminth parasitic of Rastrelliger spp. are Lechitocladium angustonum (Digenea: Hemiuridae), Lecitochirium sp. (Digenea: Hemiuridae), Prodistomum orientalis (Digenea: Lepocreadiidae) and Anisakis typica (Nematodes: Anisakidae), with 90.12% of prevalence. They are not significant different of helminth parasitic abundance from R. kanagurta and R. brachysoma, but significant in helminth species richness. This different of helminth species richness was because of L. angustonum dominances. The different location wasn’t have significant different of helminth parasitic abundance because Indonesian in the tropical zone. Anisakis species in Java sea have a same genetic with Anisakis typical and not zoonotic parasite kategories. The fish digestion was a microhabitat for helminth parasitik because they have much food stuff. The fish growth have significant different in helminth parasitic abundance and intencity. This situation was because the fish immunity development and the food habit of fish.